Matrix metalloproteinases as target genes for gene regulatory networks driving molecular and cellular pathways related to a multistep pathogenesis of cerebrovascular disease. Issue 10 (5th May 2019) - Polonikov, Alexey; Rymarova, Larisa; Klyosova, Elena; Volkova, Anastasia; Azarova, Iuliia; Bushueva, Olga; Bykanova, Marina; Bocharova, Iuliia; Zhabin, Sergey; Churnosov, Mikhail; Laskov, Vitaliy; Solodilova, Maria
Abstract: The present study investigated a joint contribution of matrix metalloproteinases (MMPs) genes to ischemic stroke (IS) development and analyzed interactions between MMP genes and genome‐wide associated loci for IS. A total of 1288 unrelated Russians (600 IS patients and 688 healthy individuals) from Central Russia were recruited for the study. Genotyping of seven single nucleotide polymorphisms (SNPs) of MMP genes (rs1799750, rs243865, rs3025058, rs11225395, rs17576, rs486055, and rs2276109) and eight genome‐wide associated loci for IS were done using Taq‐Man–based assays and MALDI‐TOF mass spectrometry iPLEX platform, respectively. Allele − 799T at rs11225395 of the MMP8 gene was significantly associated with a decreased risk of IS after adjustment for sex and age (OR = 0.82; 95%CI, 0.70‐0.96; P = 0.016). The model‐based multifactor dimensionality reduction method has revealed 21 two‐order, 124 three‐order, and 474 four‐order gene‐gene (G×G) interactions models meaningfully ( P perm < 0.05) associated with the IS risk. The bioinformatic analysis enabled establishing the studied MMP gene polymorphisms possess a clear regulatory potential and may be targeted by gene regulatory networks driving molecular and cellular pathways related to the pathogenesis of IS. In conclusion, the present study was the first to identify an association between polymorphism rs11225395 of the MMP8 gene and IS risk. The study findings also indicate that MMPs deserve special attention as a potential class of genes influencing the multistep mechanisms of cerebrovascular disease including atherosclerosis in cerebral arteries, acute cerebral artery occlusion as well as the ischemic injury of the brain and its recovery. Abstract : SNP rs11225395 of the MMP8 gene is associated with the risk of ischemic stroke. Matrix metalloproteinases (MMPs) interact to other susceptibility genes for ischemic stroke. MMPs are jointly involved in the mechanisms of ischemic stroke. MMPs are targets for gene regulatory networks related to the disease pathogenesis